Algorithms and Computation 25th International Symposium, ISAAC 2014, Jeonju, Korea, December 15-17, 2014, Proceedings - Ahn, Hee-Kap.; Shin, Chan-Su.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 25th International Symposium on Algorithms and Computation, ISAAC 2014, held in Jeonju, Korea, in December 2014. The 60 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 171 submissions for inclusion in the book. The focus of the volume in on the following topics: computational geometry, combinatorial optimization, graph algorithms: enumeration, matching and assignment, data structures and algorithms, fixed-parameter tractable algorithms, scheduling algorithms, computational complexity, computational complexity, approximation algorithms, graph theory and algorithms, online and approximation algorithms, and network and scheduling algorithms.
Computational geometry -- Combinatorial optimization -- Graph algorithms -- Enumeration, matching and assignment -- Data structures and algorithms -- Fixed-parameter tractable algorithms -- Scheduling algorithms -- Computational complexity -- Approximation algorithms, graph theory and algorithms -- Online and approximation algorithms -- Network and scheduling algorithms.
Keywords: Computer science; Data structures (Computer science).; Algorithms; Computer science -- Mathematics; Computer graphics; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Computer Graphics; Data Structures; Computer Science, general; Electronic books